Differences in demographics and clinical outcomes in older, middle-aged, and younger adults with low back pain receiving chiropractic care - L. A. Hansen; J. Hartvigsen; R. K. Jensen (Chiropractic & Manual Therapies)
Abstract Background The evidence on age-related differences in outcomes in patients seeking chiropractic care for low back pain is limited. The aims of this study were to (i) to explore differences in patient characteristics and symptoms between older, middle-aged and younger patients with LBP seeking chiropractic care, (ii) to investigate whether age was associated with changes in physical function at 2, 13 and 52 weeks follow-up and (iii) to evaluate if other specific demographic variables were associated with changes in physical function over time. Methods This observational cohort study (November 2016 to December 2018) used data from the Danish Chiropractic Low Back Pain Cohort (ChiCo). Participants ≥ 18 years seeking chiropractic care for new onset low back pain were categorised into three age groups: young adults (< 40 years), middle-aged adults (40–59 years), and older adults (≥ 60 years). Disability was assessed at baseline and at 2, 13 and 52 weeks follow-up using the Roland Morris Disability Questionnaire. Associations between age groups and disability outcomes were analysed using linear regression, while associations with demographics, and social and psychological factors were examined using backward stepwise linear regression. Results 2777 participants were included. At baseline, there were no significant differences in disability scores between age groups. Older patients reported more non-musculoskeletal comorbidities and prescription pain medication use, compared to younger and middle-aged patients. Younger patients showed higher depression and anxiety levels compared to middle-aged and older patients. Younger and middle-aged patients more frequently reported multiple musculoskeletal comorbidities than older patients. At all follow-ups, older patients had slightly higher disability scores and showed less improvement over time compared to younger and middle-aged patients, indicating a modest association between age and poorer outcomes. Higher baseline disability, more musculoskeletal comorbidities, worse self-reported health, and higher depression scores were more consistently associated with less improvement in disability over time. Conclusion Older chiropractic patients with low back pain had slightly higher disability scores compared to younger and middle-aged patients, but age was not the strongest factor associated with disability outcomes. Baseline disability, depression, self-perceived general health, and MSK comorbidities were more consistently linked to higher disability scores across all follow-up time points.